CMS 21: INTEGRATING GAME-BASED LEARNING IN BASIC AUTOMOTIVE - Jermil R. Angeles, Joel I. Alvarez, (EPRA International Journal of Research and Development (IJRD), 2023)
This study sought to determine the effectiveness of Car Mechanic Simulator 21 (CMS 21) in learning concepts in Automotive. This study described the performance of two groups of students in different skills in Automotive before and after a series of instructions using the two learning interventions (module and CMS 21) using pre-test and post-test design. This study was conducted at Nueva Ecija University of Science and Technology, and Bachelor of Science in Industrial Education (20) students served as subjects. The study used the experimental design of research. Using t-tests, results revealed that i) there is statistical evidence to reject the null hypothesis “There is no significant difference in the performances of subjects under the controlled group in the pre-test and post-test, and ii) there is statistical evidence to reject the null hypothesis There is no significant difference in the performances of subjects under the experimental group in the pre-test and post-test. Lastly, after applying statistical treatments, there is statistical evidence to reject the null hypothesis There is a significant difference in the performances of the students between the two groups after their respective interventions. Thus, the use and implementation of CMS 21 is recommended.